Intrinsic platelet reactivity before P2Y12 blockade contributes to residual platelet reactivity despite high-level P2Y12 blockade by prasugrel or high-dose clopidogrel - Frelinger III, Andrew L.; Michelson, Alan D.; Wiviott, Stephen D.; Trenk, Dietmar; Neumann, Franz-Josef; Miller, Debra L.; Jakubowski, Joseph A.; Costigan, Timothy M.; McCabe, Carolyn H.; Antman, Elliott M.; Braunwald, Eugene (Thrombosis and Haemostasis, 2011)
It was the objective of this study to determine whether the intrinsic platelet response to adenosine diphosphate (ADP) before thienopyridine exposure contributes to residual platelet reactivity to ADP despite high level P2Y12 blockade by prasugrel (60 mg loading dose [LD]), 10 mg daily maintenance dose [MD]) or high-dose clopidogrel (600 mg LD, 150 mg daily MD). High residual platelet function during clopidogrel therapy is associated with poor clinical outcomes. It remains unknown whether the relationship between platelet reactivity prior to treatment with clopidogrel (300 mg LD, 75 mg daily MD) and residual on-treatment platelet reactivity is maintained after more potent P2Y12 inhibition. PRINCIPLE-TIMI 44 was a randomised, double-blind, twophase crossover study of prasugrel compared with high-dose clopidogrel in 201 patients undergoing cardiac catheterisation for planned percutaneous coronary intervention. ADP-stimulated platelet-monocyte aggregates, platelet surface P-selectin and platelet aggregation were measured pre-treatment, during LD (6 h and 18–24 h) and MD (15 d). Correlations of pre-treatment to on-treatment values were determined by Spearman rank order. Prasugrel resulted in greater platelet inhibition than high-dose clopidogrel for each measure. However, for both drugs, pre-treatment reactivity to ADP predicted 6 h, 18–24 h and 15 day reactivity to ADP (correlations 0.24–0.62 for platelet-monocyte aggregates and P-selectin). In conclusion, a patient's intrinsic platelet response to ADP before exposure to thienopyridines contributes to residual platelet reactivity to ADP despite high level P2Y12 blockade with high-dose clopidogrel or even higher level P2Y12 blockade with prasugrel. Patients who are hyper-responsive to ADP pre-treatment are more likely to be hyper-responsive to ADP on-treatment, which may be relevant to therapeutic strategies.
Keywords: Antiplatelet agents; cardiology; clinical trials; antiplatelet drugs; platelet pharmacology